THE INFLUENCE OF EMPLOYEE PROCUREMENT, COMPENSATION, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT PT SUMBER ALFARIA TRIJAYA TBK BRANCH JEMBER - Geafa Jahjadi Gozali; Nyoman Gede Krishnabudi; Khanifatul Khusna (Program Studi Manajemen Keuangan Syariah, 2024)
This study examines and analyzes whether Employee Procurement, Compensation, and Organizational Culture affect Employee Performance at PT Sumber Alfaria Trijaya Tbk Jember Branch. The number of samples in this study used employees who worked for more than one year, as many as 93 employees of PT Sumber Alfaria Trijaya Tbk Jember Branch, because the organizational culture variable would differ in the implementation of values between new employees and old employees. The type of data used is quantitative data. Sources data using primary sources were obtained by distributing questionnaires directly and interviewing several respondents, as well as secondary data from literature studies. The analytical method used is multiple linear regression analysis using the IBM SPSS application. This study's results indicate a significant influence between Employee Procurement, Compensation, and Organizational Culture on Employee Performance at PT Sumber Alfaria Trijaya Tbk Jember Branch, which is supported by previous studies